Application of central immunologic concepts to cancer: Helping T cells and B cells become intolerant of tumors. Issue 7 (July 2014) - Anderson, Colin C.
<x xml:space="preserve">Abstract</x> CD4‐mediated T‐cell help in the activation of CD8+ T cells and B cells, through linked‐recognition of antigenic determinants, is a long‐standing concept foundational to our understanding of immunity (presence of help) versus tolerance (lack of help). Surprisingly, this function of CD4+ T cells has not been extensively examined as a means to overcome immune tolerance of the self‐antigens made by tumor cells. Hesitation to employ this powerful mechanism may be due to the potential to cause unwanted autoimmune pathology. In this issue of the European Journal of Immunology, Snook et al. [Eur. J. Immunol. 2014. 44: 1956–1966] identify a state of split tolerance, showing that CD4+ T cells specific for a number of tumor‐associated self‐antigens are robustly tolerant, while their CD8+ T‐cell and B‐cell counterparts are far less tolerant. Furthermore, the authors demonstrate that provision of linked foreign helper epitopes, such as influenza hemagglutinin, substantially enhances both CD8+ T‐cell and B‐cell responses to tumor self‐antigens without causing any overt autoimmune pathology. These findings provide a strong rationale to employ foreign helper epitopes in cancer vaccines and highlight the need to fully explore therapeutic strategies that are based on well‐established immunologic concepts.